Perylene Bisimide‐Cored Supramolecular Coordination Complexes: Interplay between Ensembles, Excited State Processes, and Aggregation Behaviors. Issue 60 (6th October 2021) - Chang, Xingmao; Wang, Zhaolong; Wang, Gang; Liu, Taihong; Lin, Simin; Fang, Yu
Abstract: Manipulating the optical properties of fluorescent species is challenging owing to complicated and tedious synthetic works. Herein, the photophysical properties of perylene bisimide (PBI) were effectively tuned by varying the geometrical arrangement of PBI moieties within supramolecular coordination complexes (SCCs), where a PBI‐based dicycle (2 ) and a trigonal prism (3 ) were generated via using a typical 90° Pt(II) reagent, cis ‐(PEt3 )2 Pt(OTf)2 ‐based coordination‐driven self‐assembly approach. The ligand, an ortho ‐tetrapyridiyl‐PBI (1 ), exhibits a moderate fluorescence quantum yield (∼13 %) and efficient inter‐system crossing (ISC). 2, however, is much more emissive with a fluorescence quantum yield of ∼41 %, and the relevant ISC process is significantly hindered. The fluorescence quantum yield of 3 is merely ∼6 % due to the observed symmetry‐breaking charge separation (SB‐CS), which turns to triplet state upon charge recombination. Interestingly, 3 could be fully transformed into 2 by simply adding a suitable amount of a 90° Pt(II)‐based neutral triangle. Moreover, 2 tends to form discrete dimers both in crystal and solution states, but 3 does not show the property. Therefore, controlling geometrical arrangement of fluorophores through coordination‐driven self‐assembly could be taken as another effective way to tune their excited state relaxation pathways and construct high‐performance optical molecular materials, which generally have to be prepared via organic synthesis. Abstract : Coordination‐driven self‐assembly was employed to manipulate inter‐/intra‐molecular interaction of PBI‐based complexes (trigonal prism and dicycle). Two complexes exhibit distinct different properties on excited state process and aggregation behaviour due to their geometrical arrangements. Trigonal prism to dicycle transformation could be tracked by fluorescence change. ( Note: ISC and SB‐CS in graphic are intersystem crossing and symmetry‐breaking charge separation, respectively.)